Estimation of Heritability and Breeding Value of Weaning Weight Garut Sheep (Case Study at UPTD-BPPTDK Margawat Garut) - Fauzan, Lutfi Ahmad; Dudi, Dudi; Arifin, Johar (Jurnal Produksi Ternak Terapan, 2024)
Sheep are one type of livestock that has great potential to be developed in Indonesia.  One of the sheep raised by Indonesian people is Garut sheep which is a Livestock Genetic Resource (SDGT) of West Java.  Researvh on estimating the breeding value of weaning weights of Garut sheep at Technical Implementation Unit of the Margawati Garut Sheep and goat Development Center (UPTD-BPPTDK) has been carried out on January 10-16, 2022. The study aims to estimate the heritability and breeding value of weaning weight of Garut Sheep at UPTD-BPPTDK Margawati Garut. The research objects used were 89 data from 25 males and 75 femaes.  The method used is descriptive analytic using analysis of the variety of the half-sib.  The fixed effects included in this analysis were sex and birth type as well as additionla parental age correction factors.  The results showed that the alleged heritability value of weaning weight 0.84 ± 0.34 was included in the high category.  The highest alleged weaning weight breeding values was obtained by sheep with ID No 11181782 of 4.654 foe male sheep and ID No 1810720 of 4.131 for female sheep.